2017
DOI: 10.1038/srep40313
|View full text |Cite
|
Sign up to set email alerts
|

A ZIP6-ZIP10 heteromer controls NCAM1 phosphorylation and integration into focal adhesion complexes during epithelial-to-mesenchymal transition

Abstract: The prion protein (PrP) evolved from the subbranch of ZIP metal ion transporters comprising ZIPs 5, 6 and 10, raising the prospect that the study of these ZIPs may reveal insights relevant for understanding the function of PrP. Building on data which suggested PrP and ZIP6 are critical during epithelial-to-mesenchymal transition (EMT), we investigated ZIP6 in an EMT paradigm using ZIP6 knockout cells, mass spectrometry and bioinformatic methods. Reminiscent of PrP, ZIP6 levels are five-fold upregulated during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 41 publications
1
39
1
Order By: Relevance
“…Zip10 is also a plausible candidate considering the regulation observed in human T cells and murine lymphocytes, and also because we found that Zip10 expression depends on the presence or absence of zinc in the extracellular medium. Moreover, Zip10 and Zip6 form heteromers in other cellular systems (7). However, in Jurkat cells, we did not observe upregulation under activation, which argues against the relevance of the heteromer in this cell type.…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…Zip10 is also a plausible candidate considering the regulation observed in human T cells and murine lymphocytes, and also because we found that Zip10 expression depends on the presence or absence of zinc in the extracellular medium. Moreover, Zip10 and Zip6 form heteromers in other cellular systems (7). However, in Jurkat cells, we did not observe upregulation under activation, which argues against the relevance of the heteromer in this cell type.…”
Section: Discussioncontrasting
confidence: 72%
“…6C, 6D), as this drug potentially allows unspecific zinc entry and activates T cells downstream of the TCR. Remarkably, the inhibition of GSK-3 kinase could not rescue Zip6KO activation, so we discard that the underlying defect in our KO cells is a dysregulation on this enzyme, a hypothesis based on the interaction between Zip6 and GSK-3b previously described (7,23) and the required kinase inactivation for the correct activation of in ZIP6KO, ZIP6KO2, and Cas9-WT cells activated for 4 and 24 h with PMA/ionomycin (n 5 3). Bonferroni-corrected ANOVA, *p , 0.05, ***p , 0.001 compared with basal conditions, # p , 0.05, ### p , 0.001 between cell lines.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations